A Rasch Analysis of the Irrational Procrastination Scale (IPS) - Shaw, Amy; Zhang, Jennifer J. (Frontiers in Psychology, 2021)
The present study analyzes the psychometric properties of the Irrational Procrastination Scale (IPS; Steel, 2002, 2010) in a sample of U.S. college students using the Rasch modeling approach. Results showed that the IPS items had a high level of reliability, good content validity, structural validity, and substantive validity, and no differential item functioning (DIF) effects in terms of gender. The IPS was found to be unidimensional, supporting the originally proposed theoretical structure by Steel (2002, 2010). Finally, psychometric implications derived from the results and study limitations are discussed; recommendations for future investigations are also offered.